DETERMINATION OF THERMAL STABILITY AND SURFACE MORPHOLOGY OF THE OBTAINED IMMOBILIZED LIGAND - Kasimov Sherzod Abduzairovich; Turaev Khayit Khudainazarovich; Djalilov Abdulakhat Turapovich; Umbarov Ibragim Amonovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article studies the thermal stability and surface morphology of the immobilized ligand obtained on the basis of in situ covalent attachment of O, O-di- (2-aminoethyl) -dithiophosphate potassium on a urea-formaldehyde matrix. As a result of the conducted thermal studies, it was determined that the resulting ligand is stable up to 128 ° C, and also has a high sorption capacity for non-ferrous metals due to its microporous surface structure.